Need Analysis in Developing Writing Instruction for Educational Short Story Writing based on Local Narratives - Sri Wulandari; Puri Bakthawar (Metathesis: Journal of English Language, Literature, and Teaching, 2024)
Writing instruction is one of the educational tools which is very important in writing courses, including creative writing. It can help students understand how to write a specific genre of text, as well as guide students in the writing process. This research aims to investigate the need for developing writing instruction for writing educational short stories based on local narratives. The need analysis includes target needs and learning needs. The type of this research is descriptive qualitative, using a questionnaire and interview as the instrument. The result of this research showed that literary aspects such as theme, plot, character, setting, point of view, and educational value needed to be strengthened. Those materials should be the priority to be implemented in writing exercises about local stories. It can be concluded that this study underlines the important role of writing instruction, especially in developing creative writing proficiency, emphasizing the need to strengthen the literary aspects of short stories.